2016
DOI: 10.1021/acsnano.6b00287
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Emitters and Silver Nanowires to Achieve Long-Range Plasmon-Mediated Fluorescence Energy Transfer

Abstract: The development of quantum plasmonic circuitry requires efficient coupling between quantum emitters and plasmonic waveguides. A major experimental challenge is to simultaneously maximize the surface plasmon propagation length, the coupling efficiency into the plasmonic mode, and the Purcell factor. Addressing this challenge is also the key to enabling long-range energy transfer between quantum nanoemitters. Here, we use a dual-beam scanning confocal microscope to carefully investigate the interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 72 publications
(152 reference statements)
1
72
1
Order By: Relevance
“…This is a pure signature of FRET, highlighting the fundamental difference with far-field radiative energy transfer. [53][54][55][56][57] In a second set of experiments, we investigate dsDNA constructs with 10.2 nm D-A separation ( Fig. 3b,d).…”
Section: Resultsmentioning
confidence: 99%
“…This is a pure signature of FRET, highlighting the fundamental difference with far-field radiative energy transfer. [53][54][55][56][57] In a second set of experiments, we investigate dsDNA constructs with 10.2 nm D-A separation ( Fig. 3b,d).…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, experimental observations of plasmon-assisted energy transfer have so far involved ensembles of fluorescent emitters [12][13] [14].…”
Section: October 18 2018mentioning
confidence: 99%
“…Previous single‐molecule imaging of EGFR dimerization has shown that there was only a 5% possibility to detect Cy3/Cy5 FRET for a single spot . Here we have observed brighter FRET signal and enhanced FRET efficiency on a plasmonic substrate, suggesting that a plasmonic substrate is especially advantageous when the FRET pair is separated by a relatively large distance, because the introduction of a plasmonic nanostructure near the FRET pair may increase the Förster distance . The self‐assembled plasmonic substrates, coupled with new fluorescence imaging technologies and introduction of emerging nanoscale fluorophores, opens the possibility for FRET imaging of live cells with improved temporal and spatial resolution …”
mentioning
confidence: 69%
“…[14][15][16][17][18][19] Single-particle experiments have suggested that the FRET channel is turned on when the LSPR of plasmonic nanocrystal lies between the emission peak of the donor and absorption peak of the acceptor or right at the emission wavelength of the acceptor, and is turned off, while the LSPR is at the emission wavelength of the donor. [20] Both theoretical and experimental studies have found that the plasmonfluorophore interactions increase the Förster distance (the distance where the possibility of energy transfer is 50%), [21][22][23][24] modify FRET efficiency, [21,[25][26][27] and enable forbidden Förster dipole-dipole energy transfer by the strongly inhomogeneous local fields. [28] Despite these advantages incurred by plasmon modulation, there is still no planar plasmonic substrate available to serve as a universal platform for tailored on-surface FRET enhancement, which is highly desirable for biosensing, optical imaging, and solar energy conversion applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation